2023
DOI: 10.3390/polym15081844
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Polysaccharide Cryogels: Interaction and In Vitro Behavior of Alginate–Gum Arabic Composites

Abstract: In the present study, polysaccharide-based cryogels demonstrate their potential to mimic a synthetic extracellular matrix. Alginate-based cryogel composites with different gum arabic ratios were synthesized by an external ionic cross-linking protocol, and the interaction between the anionic polysaccharides was investigated. The structural features provided by FT-IR, Raman, and MAS NMR spectra analysis indicated that a chelation mechanism is the main process linking the two biopolymers. In addition, SEM investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…According to the TGA thermograms in Figure 2b, the pullulan biopolymer lost approximately 75% of its mass between 300 and 350 °C, and approximately 98% of its total mass in the 360-560 °C range, thermally decomposing at the second step. The significant weight loss of 75%, specific to an exothermic phenomenon, observed in the 300-360 °C range was consistent with the literature [29,33,34]. This phenomenon is closely in line with earlier research and can be explained by the depolymerization and decomposition of the polymeric matrix at higher temperatures [35,36].…”
Section: Pullulan Cryogels As Super-macroporous Structuressupporting
confidence: 92%
“…According to the TGA thermograms in Figure 2b, the pullulan biopolymer lost approximately 75% of its mass between 300 and 350 °C, and approximately 98% of its total mass in the 360-560 °C range, thermally decomposing at the second step. The significant weight loss of 75%, specific to an exothermic phenomenon, observed in the 300-360 °C range was consistent with the literature [29,33,34]. This phenomenon is closely in line with earlier research and can be explained by the depolymerization and decomposition of the polymeric matrix at higher temperatures [35,36].…”
Section: Pullulan Cryogels As Super-macroporous Structuressupporting
confidence: 92%
“…Furter, the cytocompatibility of CR has been well-established in the literature [58,93] and has even been used effectively in clinical settings [94,95]. Similarly, all assessed gums are used extensively in the biomaterials field with an equal well-documented cytocompatibility (e.g., GA [96][97][98][99], GG [100][101][102][103][104], GK [105][106][107], GX [108][109][110]) with a diverse range of cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…44 SBF, which closely resembles the composition of human plasma, is commonly employed in vitro to mimic apatite formation in vivo. 45 Studies have shown that negatively charged groups, especially those containing phosphates, are the most effective inducers of the nucleation of CaP. 46 The presence of apatite deposits on biomaterial surfaces after immersion in SBF serves as an indicator of the potential osseointegration capabilities in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…SBF, which closely resembles the composition of human plasma, is commonly employed in vitro to mimic apatite formation in vivo . Studies have shown that negatively charged groups, especially those containing phosphates, are the most effective inducers of the nucleation of CaP .…”
Section: Discussionmentioning
confidence: 99%